Difference between mitogen-stimulated B and T cells in nonspecific binding of R-phycoerythrin-conjugated antibodies - Bohacova, Pavla; Kossl, Jan; Hajkova, Michaela; Hermankova, Barbora; Holan, Vladimir; Javorkova, Eliska (Journal of immunological methods, 2021)
Nonspecific binding of conjugated antibodies represents a critical step which could significantly influence the results of immunostaining or flow cytometry. In this respect, various staining procedures and distinct cell types can alter the results obtained with different fluorochromes. In this study, we analysed nonspecific binding of R-phycoerythrin (R-PE)-conjugated antibodies to mouse mitogen-stimulated B and T lymphocytes. The cells were fixed, permeabilized and stained using isotype control antibodies conjugated with different fluorochromes and assessed by flow cytometry. R-PE-conjugated antibodies bound to LPS-stimulated B cells, in contrast to Con A-stimulated T cells, independently of their specificity. The percentage of R-PE positive B cells varied, according to the used antibodies or the fixation/permeabilization kit. Nevertheless, up to 30% of R-PE+ B cells after staining with R-PE-conjugated isotype control antibodies was detected. Furthermore, LPS-stimulated B cells bound nonspecifically, in a dose-dependent manner, unconjugated R-PE molecules. Con A-stimulated T cells slightly bound R-PE only in high concentrations. Similarly, the antibodies conjugated with other fluorochromes showed less than 1% of nonspecific binding independently of the manufacturer of antibodies or fixation/permeabilization kits. The data demonstrated that LPS-stimulated B cells, in contrast to Con A-stimulated T cells, bind R-PE nonspecifically following formaldehyde or paraformaldehyde fixation. Therefore, the results based on the use of R-PE-conjugated antibodies should be taken with a precaution.
Keywords: Flow cytometry; Animals; Female; Mitogens; vazebná místa; fykoerythrin; ženské pohlaví; B cells; Antibodies, Monoclonal; mitogeny; Mice; Phycoerythrin; Mice, Inbred BALB C; T-lymfocyty; myši; R-phycoerythrin; myši inbrední C57BL; myši inbrední BALB C; B-Lymphocytes; Nonspecific binding; T cells; B-lymfocyty; monoklonální protilátky; T-Lymphocytes; zvířata; Mice, Inbred C57BL; Binding Sites